Esther's Town - Lee, Deemer, 1905-1979 (Book collections on Project MUSE., 2013)
Esther's Town could be "Any Town, U.S.A.," for the equals of its cast of characters can be found in any small town. And here, as usual, was the town newspaper editor, the observing eye of all the foibles and peccadillos that form any town's history. Remembering all the years with love and humor, editor Deemer Lee chronicled the forty-four years he gathered and wrote news - forty-one of them as editor and publisher of his town's newspaper. He dug into old records, recalled old times, and talked with old-timers. He illuminated the transition of Estherville, from pioneer settlement to a busy, active town